The Effect of Phosphate-Solubilizing Bacteria and IAA Producers from Cactus Rhizosphere on the Germination of Vigna sinensis L. - Muhammad Fikri Alfiansyah; Lalu Zulkifli; Dewa Ayu Citra Rasmi (Jurnal Biologi Tropis, 2023)
This study aims to examine the effect of phosphate-solubilizing bacteria and IAA producers on the germination of Vigna sinensis L. The bacteria were isolated from the cactus rhizosphere in Senteluk Village, Batulayar Subdistrict, West Lombok. The soluble phosphate was measured qualitatively and quantitatively. Qualitative measurement was based on the solubility of P in the growth medium (solid Pikovskaya) with a clear zone indicator around the bacterial colonies. The solubility of P (liquid Pikovskaya) and IAA production were measured using a spectrophotometer at wavelengths of 430 nm and 530 nm, respectively. In vitro testing of the effects of phosphate-solubilizing bacteria and IAA-producing bacteria on the germination of long beans (Vigna sinensis L.), specifically the Parade tavi variety, was conducted by soaking the long bean seeds in the bacterial suspension and then planting them on Murphy agar medium. The plant height, root length, fresh weight, and dry weight were measured and analyzed using One-Way ANOVA. The bacterial characterization included colony morphology, cell shape, and biochemical tests. The research results obtained 8 isolates that could solubilize phosphate in the low category while producing IAA and 2 other isolates that only produced IAA. Quantitative phosphate solubilization showed the highest soluble phosphate on days 4 and 6 of incubation. The highest IAA production (14.25 ppm) was achieved by the rhizosphere bacterial isolate with the code RK7. The results showed that there was an indication of the influence of phosphate solubilizing and IAA-producing bacteria isolated from the rhizosphere of cactus on Vigna sinensis L. germination, although not significantly different. This shows that local bacterial isolates are quite potential as a source of biofertilizer development in the future.